The Consistency of Ibn Ḥibbān to the Ḥujjiyyah Narrated by al-Mudallīsīn in Ṣaḥīḥ Ibn Ḥibbān - Osman, Mohd Nor Adli bin; Ramle, Muhamad Rozaimi bin (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
Imam Ibn Ḥibbān was a prominent scholar in various Islamic sciences, particularly ḥadīth. Among his major works is Ṣaḥīḥ Ibn Ḥibbān. In this book, as well as in other works such as al-Thiqāt and al-Majrūḥīn min al-Muḥaddithīn, he explicitly stated that he would not accept ḥadīth narrations classified as riwāyah al-mudallas. However, instances of such narrations appear in Ṣaḥīḥ Ibn Ḥibbān, indicating differences in the methodology applied across these works. Furthermore, notable discrepancies exist between Ibn Ḥibbān's definition of riwāyah al-mudallas and those of other muḥaddithīn. This study aims to examine Ibn Ḥibbān 's definition of riwāyah al-mudallas and evaluate the consistency of his methodology in addressing these narrations. To achieve these objectives, the research employs a qualitative approach, collecting data primarily from major ḥadīth sources and analyzing them using both inductive and deductive methods. The findings of this study reveal that Ibn Ḥibbān defines al-mudallis as a narrator who reports from a teacher, they have met but narrates reports they have not directly heard or a narrator who reports from a contemporary without ever meeting them, using terminology that implies otherwise. Moreover, Ibn Ḥibbān followed his methodological principles and objectives when including riwāyah al-mudallas in his Ṣaḥīḥ. This study contributes to a deeper understanding of the concept of riwāyah al-mudallas among ḥadīth scholars and Ibn Ḥibbān’s approach in addressing these narrations in his collection.